Politik Bahasa Nasional dan Daerah dalam Perspektif Orang Lamaholot menjadi Orang Indonesia - Sebastianus Fernandez (Masyarakat Indonesia, 2010)
This article constitutes a summary of a dissertation entitled National and Regional Language Politics in the Perspective of Lamaholot People of Becoming Indonesian. The purpose of the research was to reveal and describe the impact of Indonesian national language politics on the nationality and the ethnic sentiment of the native speakers of Lamaholot. The method employed in the research is qualitative in its nature. This study results in some findings, among others, are: (i) the Indonesia language politics is successful in promoting Indonesian language as the language of unity among Indonesian people and, at the same time, it is successful in building Indonesian linguistic nationalism among West Lamaholot language communities, (ii) the language policy aiming at linguistic homogeneity within Indonesian multi-ethnic societies cannot get rid of Lamaholot language and its ethnic sentiment; (iii) the communities are resistant to the policy which promotes some asymmetric, feudal and non-egalitarian state language; (iv) the older generation are resistant to the use of Indonesian language in cultural and traditional domains; and (v) the communities can wisely distinguish between the use of Indonesian language and the use of Lamaholot in its appropriate domain. This study brings about some theoretical understandings related to the concepts of nationality, ethnicity and language policy in a modern nation-state. Firstly, it reveals that the language policy has failed to make the use of minority languages come to an end. Secondly, to promote a language of unity among the societies in a multi-ethno-linguistic sphere is of paramount importance. But, this does not signify that the national language can replace all functions of the other minority languages. Finally, ethnicity and nationality in multi-ethnic societies within a modern nation-state do not always become two conflicting and contradicting entities. Ethnicity and nationality may coexist peacefully if they are properly managed.Keywords: Language Politics, assimilationist language policy, ethnicity, nationality, nation-state, linguistic homogeneity